Successful robotic gastrectomy does not require extensive laparoscopic experience - An, Ji Yeong; Kim, Su Mi; Ahn, Soohyun; Choi, Min Gew; Lee, Jun Ho; Sohn, Tae Sung; Bae, Jae Moon; Kim, Sung (Journal of Gastric Cancer, 2018)
Purpose: We evaluated the learning curve and short-term surgical outcomes of robot-assisted distal gastrectomy (RADG) performed by a single surgeon experienced in open, but not laparoscopic, gastrectomy. We aimed to verify the feasibility of performing RADG without extensive laparoscopic experience. Materials and Methods: Between July 2012 and December 2016, 60 RADG procedures were performed by a single surgeon using the da Vinci® Surgical System (Intuitive Surgical). Patient characteristics, the length of the learning curve, surgical parameters, and short-term postoperative outcomes were analyzed and compared before and after the learning curve had been overcome. Results: The duration of surgery rapidly decreased from the first to the fourth case; after 25 procedures, the duration of surgery was stabilized, suggesting that the learning curve had been overcome. Cases were divided into 2 groups: 25 cases before the learning curve had been overcome (early cases) and 35 later cases. The mean duration of surgery was 420.8 minutes for the initial cases and 281.7 minutes for the later cases (P<0.001). The console time was significantly shorter during the later cases (168.6 minutes) than during the early cases (247.1 minutes) (P<0.001). Although the volume of blood loss during surgery declined over time, there was no significant difference between the early and later cases. No other postoperative outcomes differed between the 2 groups. Pathology reports revealed the presence of mucosal invasion in 58 patients and submucosal invasion in 2 patients. Conclusions: RADG can be performed safely with acceptable surgical outcomes by experts in open gastrectomy.
Keywords: Gastrectomy; Learning curve; Robotic surgical procedures; Stomach neoplasms